When Do Team Members Share the Lead? A Social Network Analysis - Tillmann, Sebastian; Huettermann, Hendrik; Sparr, Jennifer L.; Boerner, Sabine (Frontiers in Psychology, 2022)
Shared leadership is not only about individual team members engaging in leadership, but also about team members adopting the complementary follower role. However, the question of what enables team members to fill in each of these roles and the corresponding influence of formal leaders have remained largely unexplored. Using a social network perspective allows us to predict both leadership and followership ties between team members based on considerations of implicit leadership and followership theories. From this social information processing perspective, we identify individual team members’ political skill and the formal leaders’ empowering leadership as important qualities that facilitate the adoption of each the leader and the follower role. Results from a social network analysis in a R&D department with 305 realized leadership ties support most of our hypotheses.